Assessment of Liver Fibrosis with Diffusion-Weighted Magnetic Resonance Imaging Using Different b-values in Chronic Viral Hepatitis - Kocakoc, Ercan; Bakan, Ayse Ahsen; Poyrazoglu, Orhan Kursat; Dagli, Adile Ferda; Gul, Yeliz; Cicekci, Mehtap; Bahcecioglu, Ibrahim Halil (Karger, 2015)
Objective: To examine the effectiveness of apparent diffusion coefficient (ADC) values and to compare the reliability of different b-values in detecting and identifying significant liver fibrosis. Subjects and Methods: There were 44 patients with chronic viral hepatitis (CVH) in the study group and 30 healthy participants in the control group. Diffusion-weighted magnetic resonance imaging (DWI) was performed before the liver biopsy in patients with CVH. The values of ADC were measured with 3 different b-values (100, 600, 1,000 s/mm(2)). In addition, liver fibrosis was classified using the modified Ishak scoring system. Liver fibrosis stages and ADC values were compared using areas under the receiver-operating characteristic (ROC) curve. Results: The study group's mean ADC value was not statistically significantly different from the control group's mean ADC value at b = 100 s/mm(2) (3.69 +/- 0.5 x 10(-3) vs. 3.7 +/- 0.3 x 10(-3) mm(2)/s) and b = 600 s/mm(2) (2.40 +/- 0.3 x 10(-3) vs. 2.5 +/- 0.5 x 10(-3) mm(2)/s). However, the study group's mean ADC value (0.99 +/- 0.3 x 10(-3) mm(2)/s) was significantly lower than that of the control group (1.2 +/- 0.1 x 10(-3) mm(2)/s) at b = 1,000 s/mm(2). With b = 1,000 s/mm(2) and the cutoff ADC value of 0.0011 mm(2)/s for the diagnosis of liver fibrosis, the mean area under the ROC curve was 0.702 +/- 0.07 (p = 0.0015). For b = 1,000 s/mm(2) and the cutoff ADC value of 0.0011 mm(2)/s to diagnose significant liver fibrosis (Ishak score = 3), the mean area under the ROC curve was 0.759 +/- 0.07 (p = 0.0001). Conclusion: Measurement of ADC values by DWI was effective in detecting liver fibrosis and accurately identifying significant liver fibrosis when a b-value of 1,000 s/mm(2) was used. (C) 2015 S. Karger AG, Basel
Keywords: Hepatitis; Fibrosis; Liver; Diffusion-weighted imaging